The Influence of Education and Training, Competence and Motivation on The Performance of Employees of The BKKBN Representative Office of Jambi Province - Azizah, Liza (Indonesian Educational Administration and Leadership Journal (IDEAL), 2024)
Quantitative research aims to describe the positive influence between education and training (training), competence and motivation with the performance of employees of the Jambi Province BKKBN. Respondents of this study amounted to 84 people (consisting of ASN and Non ASN). The data in this study came from the results of the questionnaire tabulation using the SmartPLS application calculation method. Based on the results of the study, it was concluded that there was a positive influence on Training, Competence and Work Motivation together on Employee Performance. Through the results of hypothesis testing in PLS obtained 71.7% so that it can be concluded that Training, Competence and Work Motivation have a positive influence on employee performance. The amount of the effective contribution of Training and Education to Employee Performance is 53.6%, Competence to Employee Performance is 65.7% and Work Motivation to Employee Performance is 76%. While the remaining 28.3% came from other variables not examined in this study.